Compressive properties of magnesium alloy AZ91D at high strain rate - Ren, Jia (2010)
The Split Hopkinson Pressure Bar test is the most commonly used method for determining material properties under extreme loading conditions. The bar also provides relatively good accuracy when the equipments are calibrated correctly. The analysis of the mechanical properties of the specimens from the voltage generated by the oscilloscope is very crucial in this project. The oscilloscope datas’ are used to determine mechanical properties such as the maximum stress, maximum strain, strain rate and the stress-strain relationship.